Strengthening Environmental Education through IoT-Based Smart Trash Bins - Hermawan, Indra; Yulianti, Susana Dwi; Malik Matin, Iik Muhamad; Zain, Ayu Rosyida; Wirawan, Chandra; Abidin, Iqbal Rizki; Azkiya, Satria Azkal; Bisawab, Muhammad Salman; Tuzahra, Alifia; Aldrine, Zefanya; Yudha, Muhammad Dhafa Ragana (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to support environmental sustainability education by implementing a Smart Trash Bin system based on Internet of Things (IoT) technology at Sekolah Alam Indonesia, Cibinong. The initiative followed a structured Participatory Action Research (PAR) approach consisting of five stages: engagement, co-development, implementation, evaluation, and feedback. A technical team developed the system from Politeknik Negeri Jakarta. It integrated ultrasonic and load-cell sensors with ESP32 microcontrollers and wireless data transmission to enable real-time monitoring of waste volume and weight. In parallel, the Environmental and Forestry Agency (DLHK) of Depok City delivered a seminar on waste ecosystem management to improve knowledge among teachers and staff. Evaluation through pre- and post-test questionnaires showed that participants' knowledge scores enhanced from 13.78 to 15.61 (out of 17), while their environmental attitudes remained consistently high. This project demonstrates a scalable model for integrating technology and environmental education in schools